(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the importance of education within the organization? Purpose: The purpose and objective of the research is to examine and present education within the organization and how to education affects on the performance and on the profits of the company. The objective of the task is to examine the education of employees for achieving business excellence and how the organization meets the needs and expectations of employees, and determine what is the process of acquiring and developing knowledge for the successful operation of the organization. Method: Quantitative - survey, qualitative – interview Results: The concrete examples or development organizations, opinion based on the profession. The results showed that the education within the organization is essential and that the future of companies largely depends on motivated and educated employees, who are able to quickly react and adapt to a changing business environment. Organization: Education is intended to all employees within the organization. Company: By education we want to influence on the entire organization, in terms of development. The originality: Research is original. Restrictions/further research: Limits of the study is that we deal with only a limited number of resources.